2007
DOI: 10.1021/jp075144f
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemistry, Bond Energies, and Internal Rotor Potentials of Dimethyl Tetraoxide

Abstract: Thermochemical properties of dimethyl tetraoxide (CH(3)OOOOCH(3)), the dimer of the methylperoxy radical, are studied using ab initio and density functional theory methods. Methylperoxy radicals are known to be important intermediates in the tropospheric ozone cycle, and the self-reaction of methylperoxy radicals, which is thought to proceed via dimethyl tetraoxide, leads to significant chain radical termination in this process. Dimethyl tetraoxide has five internal rotors, three of them unique; the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 77 publications
4
21
0
Order By: Relevance
“…Goldsmiths et al also reported the standard entropy of methoxy, ethoxy, and n -propoxy radicals as (in cal mol –1 K –1 ) 54.4 ± 0.3, 66.8 ± 1.0, and 75.7 ± 1.5, respectively, which also agree with group additivity calculation. Burke et al recommended 66.11 cal mol –1 K –1 as the standard entropy for ethoxy radical and suggested 74.5 cal mol –1 K –1 for the n -propoxy radical; they calculated 75.29 cal mol –1 K –1 for the n -propoxy radical based on group additivity. In this study, we report the standard entropy of methyl hydroperoxide, ethyl hydroperoxide, n -propyl hydroperoxide, and n -butyl hydroperoxide as (in cal mol –1 K –1 ) 66.27, 77.08, 87.35, and 97.71, respectively, which also follow group additivity.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goldsmiths et al also reported the standard entropy of methoxy, ethoxy, and n -propoxy radicals as (in cal mol –1 K –1 ) 54.4 ± 0.3, 66.8 ± 1.0, and 75.7 ± 1.5, respectively, which also agree with group additivity calculation. Burke et al recommended 66.11 cal mol –1 K –1 as the standard entropy for ethoxy radical and suggested 74.5 cal mol –1 K –1 for the n -propoxy radical; they calculated 75.29 cal mol –1 K –1 for the n -propoxy radical based on group additivity. In this study, we report the standard entropy of methyl hydroperoxide, ethyl hydroperoxide, n -propyl hydroperoxide, and n -butyl hydroperoxide as (in cal mol –1 K –1 ) 66.27, 77.08, 87.35, and 97.71, respectively, which also follow group additivity.…”
Section: Results and Discussionmentioning
confidence: 99%
“…There are a number of calculated values for the enthalpy of formation data on smaller (C1–C6) alkyl peroxides and the corresponding peroxy radicals, and these values are widely used and applied in modeling combustion , and atmospheric chemistry . They are also used in understanding oxidation chemistry of organic chemicals to form hydroperoxides for synthesis…”
Section: Introductionmentioning
confidence: 99%
“…The B3LYP method has proven its accuracy in determining geometrical parameters [29,30], electronic energies and thermochemical properties [31][32][33][34], and is used widely for studying structures and the stability of large molecules, fullerenes, and supramolecules [22,29,35,36]. The basis sets 6-31G and 6-31G(d) have also been recommended for purposes such as the present study.…”
Section: Methodsmentioning
confidence: 99%
“…(A1). Spectroscopic and potential constants are listed in Table I 22,28–48. The H m, i – H m, j interaction in CH 3 can be estimated in terms of the Lennard–Jones parameters for CH 3 ⋅⋅⋅CH 3 , ε H italicm H m / k B = 144 K and σ H italicm H m = 3.8 Å 49, where i , j are deleted for convenience.…”
Section: Collision Model and Methodsmentioning
confidence: 99%